Assessment Of Agnibala In Vataj Grahani Before And After Ayurvedic Intervention. - Rahi, Saurabh; Sharma, Rashi (Journal of Neonatal Surgery, 2025)
Background:Vataj Grahani is a chronic gastrointestinal disorder described extensively in Ayurvedic texts, primarily caused by Agni Dusti. Its clinical presentation resembles Irritable Bowel Syndrome (IBS) as per modern medicine. Restoration of Agni is central to treatment, and Kshar Ghrit—having Deepan-Pachana and Agni-balancing properties—is traditionally recommended. This study aimed to assess Agnibala in Vataj Grahani patients before and after Ayurvedic intervention using Kshar Ghrit. Methods:A total of 45 clinically diagnosed Vataj Grahani patients were selected according to inclusion and exclusion criteria. Each patient received 10 ml Kshar Ghrit twice daily after meals for 3 months, with monthly follow-ups. Agnibala was assessed using a standard questionnaire-based proforma developed by Singh A. et al. (IMS BHU). Eight classical symptoms of Vataj Grahani and Rome IV criteria for IBS were incorporated for evaluation. Data were statistically analyzed. Results:Significant improvement was observed in all major symptoms. Abdominal pain reduced to Grade 0 in 73.3% patients; increased stool frequency, loose mucoid stools, bloating, constipation-predominant stools, and dryness showed substantial improvement. Vomiting resolved completely. Overall Agnibala improved markedly post-intervention, with a shift toward balanced digestive function. Conclusion:Kshar Ghrit proved effective in enhancing Agnibala and relieving symptoms of Vataj Grahani. The intervention demonstrated significant improvement in digestive function and Vata-related symptoms, indicating strong potential for managing functional gastrointestinal disorders within Ayurvedic practice